Engineering the properties of eco-friendly medium density fibreboards bonded with lignosulfonate adhesive : Dizajniranje svojstava ekološki prihvatljivih ploča vlaknatica srednje gustoće proizvedenih uporabom lignosulfonatnog ljepila - Savov, Viktor (Array, 2020)
Free formaldehyde emissions from wood-based panels, especially in indoor applications, pose serious risks to human health at certain concentrations. Prolonged exposure to formaldehyde can cause adverse health effects including eye, nose and throat irritation, other respiratory symptoms and cancer. As a consequence, new formaldehyde emission limits for composite wood products were established in Europe, USA and Japan. This, together with the stricter environmental legislation are the main driving factors for shifting the scientific and industrial interest from the traditional formaldehyde-based synthetic resins to the new bio-based adhesives for production of eco-friendly wood-based panels. The lignin-based products are one of the most prospective ecological alternatives to the traditional formaldehyde resins. The main interest in lignin is due to its phenolic structure with several favourable properties for the formulation of wood adhesives such as high hydrophobicity and low polydispersity. The present article is aimed at studying the possibilities for using lignosulfonate as an adhesive for the production of eco-friendly MDF. Regression models describing the impact of lignosulfonate concentration and hot pressing temperature on the exploitation properties of MDF panels were developed. The individual and combined impact of both factors was analysed in order to determine the optimal exploitation properties of the panels.